Somatostatin Analogs Therapy in Gastroenteropancreatic Neuroendocrine Tumors: Current Aspects and New Perspectives - Baldelli, Roberto (Frontiers in Endocrinology, 2014)
Gastroenteropancreatic neuroendocrine tumours (GEP NETs) are rare tumours that present many clinical features secreting peptides and neuroamines that cause distinct clinical syndromes such as carcinoid syndrome. However most of them are clinically silent until late presentation with mass effects. Surgical resection is the first line treatment for a patient with a GEP NET while in metastatic disease multiple therapeutic approaches are possible. GEP NETs are able to express somatostatin receptors (SSTRs) bounded by somatostatin (SST) or its synthetic analogues, although the subtypes and number of SSTRs expressed is very variable. In particular somatostatin analogues are used frequently to control hormone-related symptoms while their anti-neoplastic activity seems to result prevalently in tumour stabilisation. Patients who fail to respond or cease to respond to standard SST analogues treatment seem to have a response to higher doses of these drugs. For this reason the use of higher doses of somatostatin analogues will probably improve the clinical management of these patients.